A PSR single-stage flyback LED driver with simple line regulation and quasi-resonant operation - 聂卫东 于宗光 王海兵 郭斌 滕龙 杨力航 (Journal of semiconductors, 2014)
A single-stage flyback driving integrated circuit （IC） for light-emitting diodes （LEDs） is proposed. With an average primary-side current estimation and negative feedback networks, the driver operates in the boundary conduction mode （BCM）, while the output current can be derived and regulated precisely. By means of a simple external resistor divider, a compensation voltage is produced on the ISEN pin during the turn-on period of the primary MOSFET to improve the line regulation performance. On the other hand, since the delay time between the time that the secondary diode current reaches zero and the turn-on time of the MOSFET can be automatically adjusted, the MOSFET can always turn on at the valley voltage even if the inductance of the primary winding varies with the output power, resulting in quasi-resonant switching for different primary inductances. The driving IC is fabricated in a Dongbu HiTek＇s 0.35μm bipolar-CMOS-DMOS process. An 18 W LED driver is finally built and tested. Results show that the driver has an average efficiency larger than 86%, a power factor larger than 0.97, and works under the universal input voltage （85-265 V） with the LED current variation within ±0.5%.